Characteristics of The Patients with Low Back Pain in The Medical Rehabilitation Clinic, Dr. Ramelan Naval Hospital Surabaya - Wijayaningrum, Lena; Setianingsih, Herin; Rahayu, Agustin Silfi (Oceana Biomedicina Journal, 2019)
Background : The total number of visits of patients with complaints of low back pain in the Medical Rehabilitation Subdepartment of dr. Ramelan Naval Hospital Surabaya from January to November 2018 was 38.7% of all visits. Low back pain is a symptom, not a disease, which is defined as pain between the edge of the ribs and the gluteus fold which can be caused by a variety of causes. It is important to know how the characteristics of LBP sufferers.Material and Methods : This study was a descriptive study, Medical records from the LBP population in July to September 2018 are used, at the Dr. Ramelan Hospital RSAL Medical Rehabilitation Clinic, with sample criteria: There are main symptoms of pain or other unpleasant feelings in the lower spine and surrounding areas. Results : 152 data were analyzed from July to September 2018, patients with pain complaints were (86.84%). The data obtained showed patients with hypertensive comorbidities 30, Diabetes Mellitus 26, and Osteoarthritis 20.Conclusion : Characteristics of patients diagnosed with Low Back Pain (LBP) at the RSAL Medical Rehabilitation Clinic Dr. Ramelan Surabaya is aged 51-60 years, many suffer from women, 80 percent complain of pain, accompanied by hypertensive comorbidities, Diabetes Melitus and Osteoarthritis. Keywords : Low back pain (LBP), pain, comorbidities